+0  
 
+1
232
1
avatar

3x+11y=4

-2x-6y=0

This is for algebra two and I need to use elimination so idk :/

Guest Oct 5, 2017
 #1
avatar
0

Solve the following system by elimination:
{3 x + 11 y = 4 | (equation 1)
-2 x - 6 y = 0 | (equation 2)

Add 2/3 × (equation 1) to equation 2:
{3 x + 11 y = 4 | (equation 1)
0 x+(4 y)/3 = 8/3 | (equation 2)

Multiply equation 2 by 3/4:
{3 x + 11 y = 4 | (equation 1)
0 x+y = 2 | (equation 2)

Subtract 11 × (equation 2) from equation 1:
{3 x+0 y = -18 | (equation 1)
0 x+y = 2 | (equation 2)

Divide equation 1 by 3:
{x+0 y = -6 | (equation 1)
0 x+y = 2 | (equation 2)

x = -6      and       y = 2

Guest Oct 5, 2017

8 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.